Efeitos dos parâmetros de usinagem no acabamento superficial de materiais cerâmicos a verde - Gonçalves Júnior, Marcos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The machining of green ceramic has benn investigated as a method for manufacturing of complex shapes. Such method provides a possible alternative for manufacturing of ceramic of complex geometry with dimensions close to the final, due to low mechanical strength, presenting advantages in terms of cost-benefit and improvement surface finishing compared to machining performed only after the sintering. In this work, the forces of machining of green ceramic workpiece and analyzed its correlation with the cutting parameters and surface finishing were measured. The correlation between the cutting power and removal rate are important parameters in order to define the project in ceramic products, in which inadequate parameters can produce excessive damage to the work piece surface. The present paper aimed the elaboration and conception of data acquisition system of the machining forces, using a dynamometer three coordinates for monitoring the cutting forces, feed and depth. For this purpose, cylindrical speciments of alumina 99.8% purity were conformed into isostatic press at 200 MPa, being turned with different cutting parameters by three types of cermet tool under machining constant conditions. Efforts were confronted with variables such as finishing and surface roughness, tip radius and wear of the cutting tool and temperature during the machining, registered through a microtermopar inserted next to tip of the cutting tool. The results showed a strong influence of the wear of the cutting tool in increased efforts and surface finish, as well as the radius of the tool tip had influence on surface finishing and in the tool life. If was verified that the depth of cut had no significant effect on the surface quality, being the cutting speed and feed the variables that had greater effect on the finishing. The feed force showed major increase efforts and the force of depth minor increments during the machining. The recorded temperature did not...

A usinagem de cerâmica verde tem sido investigada como um método para fabricação de formas complexas. Tal método fornece uma alternativa possível para a fabricação de cerâmica de geometria complexa com dimensões próximas as finais, devido à baixa resistência mecânica, apresentando vantagens em termos de custo benefício e melhoria no acabamento superficial, em comparação com a usinagem realizada somente após a sinterização. Neste trabalho foram medidas as forças de usinagem de corpos cerâmicos a verde, e analisado a sua correlação com os parâmetros de corte e com o acabamento superficial. A correlação entre a potência de corte e a taxa de remoção são parâmetros inadequados podem produzir danos superficiais excessivos na peça. O presente trabalho objetivou a elaboração e a concepção de um sistema de aquisição de dados das forças de usinagem, utilizando um dinamômetro de três coordenadas, para monitorar as forças de corte, avanço e profundidade. Para isso, corpos de prova cilíndricos de alumina de 99,8% de pureza foram conformados em prensa isostática a 200 MPa, sendo torneados com diferentes parâmetros de corte por três tipos de ferramenta de cermet sob condições constantes de usinagem. Foram confrontados com os esforços variáveis como acabamento e rugosidade superficial, raio de ponta e desgaste da ferramenta de corte e a temperatura durante a usinagem, registrada através de um microtermopar inserido próximo da ponta da ferramenta de corte. Os resultados mostraram forte influência do desgaste da ferramenta de corte no incremento dos esforços e no acabamento superficial, como também, o raio de ponta da ferramenta teve influência no acabamento superficial e na vida útil da ferramenta. Foi verificado que a profundidade de corte não teve efeito considerável sobre a qualidade da superfície, sendo a velocidade de corte e de avanço as variáveis que apresentaram maior efeito no acabamento...
Keywords: Ceramica; Usinagem; Processos de fabricação; Ceramics (Art)